2010
DOI: 10.5802/aif.2582
|View full text |Cite
|
Sign up to set email alerts
|

Spherical gradient manifolds

Abstract: 18 pagesNous étudions l'action d'un groupe réel-réductif $G=K\exp(\lie{p})$ sur une sous-variété réel-analytique $X$ d'une variété kählérienne $Z$. Nous supposons que l'action de $G$ peut être prolongée à une action holomorphe du groupe complexifié $G^\mbb{C}$ telle que l'action d'un sous-groupe maximal compact de $G^\mbb{C}$ soit hamiltonienne. L'application moment $\mu$ induit une application gradient $\mu_\lie{p}\colon X\to\lie{p}$. Nous montrons que $\mu_\lie{p}$ separe les orbites de $K$ si et seulement s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Let H ⊂ G be a closed subgroup such that X = G/H is a G-gradient manifold with gradient map µ p : X → p. We say that X = G/H is spherical if a minimal parabolic subgroup of G has an open orbit in X. In this case we call H a spherical subgroup of G and h a spherical subalgebra of g. As shown in [MS10] sphericity of X is equivalent to the fact that µ p almost separates the K-orbits in X, i.e., that the map X/K → p/K induced by µ p : X → p has discrete fibers.…”
Section: Characterization Of Spherical Homogeneous Gradient Manifoldsmentioning
confidence: 99%
See 3 more Smart Citations
“…Let H ⊂ G be a closed subgroup such that X = G/H is a G-gradient manifold with gradient map µ p : X → p. We say that X = G/H is spherical if a minimal parabolic subgroup of G has an open orbit in X. In this case we call H a spherical subgroup of G and h a spherical subalgebra of g. As shown in [MS10] sphericity of X is equivalent to the fact that µ p almost separates the K-orbits in X, i.e., that the map X/K → p/K induced by µ p : X → p has discrete fibers.…”
Section: Characterization Of Spherical Homogeneous Gradient Manifoldsmentioning
confidence: 99%
“…In [HS07] it has been shown that the so-called gradient maps are the right analogue for moment maps when one is interested in actions of a real reductive group G = K exp(p). Spherical gradient manifolds have been introduced in [MS10] in order to carry over Brion's theorem to the real reductive case. To be more precise, we call a G-gradient manifold X ⊂ Z with gradient map µ p : X → p spherical if a minimal parabolic subgroup of G has an open orbit in X.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the founding article of R. Richardson and P. J. Slodowy [20] where they showed that the Kempf-Ness theorem extends to representations of real reductive groups, many authors have studied extensions of geometric invariant theory to the real framework [6,8,15,4,3].…”
Section: Introductionmentioning
confidence: 99%